Sorting via screening versus signaling: A theoretic and experimental comparison - Werner Güth; Fabian Winter (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
Similar to Kübler et al. (2008, GEB 64, p. 219-236), we compare sorting in games with asymmetric incomplete information theoretically and experimentally. Rather than distinguishing two very different sequential games, we use the same game format and capture the structural difference of screening and signaling only via their payoff specification. The experiment thus relies on the same verbal instructions. Although the equilibrium outcomes coincide, greater efficiency losses off the equilibrium play due to sorting under signaling, compared to screening, is predicted and confirmed experimentally.
Keywords: C9; D82; J24; J40; 330; off-equilibrium play; screening; signaling; sorting; wage bargaining